1987
DOI: 10.1111/j.1476-5381.1987.tb11327.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of agonists on the components of the cardiac muscarinic receptor

Abstract: 1 The binding of eleven agonists to muscarinic receptors in the rat heart has been measured in competition with [3H]-N-methylscopolamine. 2 Full analysis of binding required the resolution of three components (SH, H and L). 3 The proportion of the H component was independent of agonist structure. The proportion of the SH component ranged from 2-36% of the total and was dependent on the agonist. The proportion of the L component varied in a complementary way from 59-22% of the total. 4 The ratios of the affinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The pattern of latent sites and noncompetitive effects exhibited by N-methylscopolamine and quinuclidinylbenzilate is essentially the same as that found previously in two different preparations from porcine atria: a solubilized extract in cholate-NaCl ( 29) and an affinity-purified complex of receptor and G protein (17). Similarly, the GMP-PNPsensitive dispersion of affinities revealed by oxotremorine-M mimics in some detail the pattern described previously for agonists at the muscarinic receptor in myocardial membranes from dog (10), rat (64), and hamster (6,16). In common with the receptor in membranes from hamster heart (6), at least four classes of sites are required to account empirically for the present data in terms of Scheme 1: three classes are observed in the absence of GMP-PNP (K A1 , K A2 , K A3 ); a fourth class arises from a nucleotide-dependent increase in the value of K A2 , and the effect is accompanied by a net interconversion of sites from the state of highest affinity (K A1 ) to that of lowest affinity (K A3 ).…”
Section: Discussionsupporting
confidence: 84%
“…The pattern of latent sites and noncompetitive effects exhibited by N-methylscopolamine and quinuclidinylbenzilate is essentially the same as that found previously in two different preparations from porcine atria: a solubilized extract in cholate-NaCl ( 29) and an affinity-purified complex of receptor and G protein (17). Similarly, the GMP-PNPsensitive dispersion of affinities revealed by oxotremorine-M mimics in some detail the pattern described previously for agonists at the muscarinic receptor in myocardial membranes from dog (10), rat (64), and hamster (6,16). In common with the receptor in membranes from hamster heart (6), at least four classes of sites are required to account empirically for the present data in terms of Scheme 1: three classes are observed in the absence of GMP-PNP (K A1 , K A2 , K A3 ); a fourth class arises from a nucleotide-dependent increase in the value of K A2 , and the effect is accompanied by a net interconversion of sites from the state of highest affinity (K A1 ) to that of lowest affinity (K A3 ).…”
Section: Discussionsupporting
confidence: 84%
“…The receptor is functionally partitioned into three affinity classes, the abundance of which is independent of agonist binding. This model is mathematically homologous to the three-state binding models of Wong et al (1986) andBurgen (1987). Even though this parameter set satisfactorily accommodates the carbamylcholine binding data presented here, it does not accommodate data indicating that the binding of BTX to sodium channels is modulated by the presence of muscarinic agonists Cohen-Armón et al, 1988).…”
Section: Resultsmentioning
confidence: 75%
“…More recently, Ehlert (1985) proposed a similar model for ligandlinked interaction between muscarinic receptors and a single G-protein, according to which the complex of receptor and G-protein (RG) has a higher affinity for agonist than receptor alone (R). Guanine nucleotides are postulated to lower the overall affinity of receptor for agonist by destabilizing the interaction between receptor and G-protein, thus converting the higher affinity RG into the lower affinity R. This model has been subsequently explored and rejected by Wong et al (1986) andBurgen (1987) as being inadequate to accommodate muscarinic receptor binding data from their respective laboratories. In preliminary calculations, we found that the ternary complex model may be fit to the data analyzed here but only if agonist binding constants for each of the two receptor substates in this model (R and RG) are allowed to vary substantially.…”
mentioning
confidence: 99%
“…Comparable afKnity ratios and fractions of the three receptor subpopulations, consistent with the proposition that there is a major component with high affinity and minor components with low and superhigh afKnity, were previously found in rat heart for a series of seven different muscarinic receptor agonists. 26 On the other hand, in cerebral cortex (MI ) and salivary glands (M3), the binding data for (+ )-1 were found to fit a two-binding site model best, yielding two fractions of receptor subpopulations, corresponding to high 0 and low (L) component sites ( Table 3). The curve indicates the computer fit of the experimental data points of a representative experiment after correction for the radioligand occupancy shift, according to a three-binding site model with visualization of the individual components of the curve for agonist states.…”
Section: Muscarine Isomersmentioning
confidence: 99%
“…In summary, as expected, the isomer corresponding to the natural muscarine [( +)-11 was the only one to show remarkable functional and molecular pharmacological activities. In addition, in the binding studies, it demonstrated receptor selectivity and recognized three affinity states of the M2 receptor, thus being in the class of full muscarinic agonists comprising acetylcholine, carbachol, furmethide, and methylfurmethide, 26 and two affinity states for the M1 and M3 receptors. On the other hand, its enantiomer ( -)-1 bound to two states of the M2 receptor and in this respect acted more like pilocarpine,26 a partial agonist, and recognized only a single site in the cerebral cortex and salivary glands.…”
Section: Muscarine Isomersmentioning
confidence: 99%